REMARKS ON THE GEOGRAPHY OF BRONZE AGE SITES IN CENTRAL ASIA - Kenjaeva N.T. (TARIXIY TADQIQOTLAR, 2023)
The Bronze Age is a historical period in which important cultural innovations took place in the history of mainkind. The study of the geography of the archaeological monuments of this period is of great scientific importance. In the archeology of Central Asia, the issues of zoning of ancient monuments have attracted the attention of researchers for many years. The collected materials were used to register the monuments, determine their geographical distribution, record their location along trade and cultural communication routes, and study some issues of historical geography. However, archeological cartography data is extremely important in researching the problems of economic-cultural types, formation of historical-cultural regions, and ethnic geography. On the basis of archeological data, it is possible to study the geography of monuments and restore maps of archaeological monuments. The article focuses on these aspects.